Early Dangling Protocol Post Lower Extremity Free Flap Surgery: An Evidence-based Case Report - Atmodiwirjo, Parintosa; Aditya, Timothy; Tafdhil Tardha, Muhammad; Nazwan Sani, Fadli (Jurnal Plastik Rekonstruksi, 2023)
Background: Free flap is tissue transplantation by including its feeding artery from one body part to another. Intravascular thrombosis is the main obstacle commonly faced in the anastomosed part. Yet, postoperative extremity mobilization has widely become the main question related to flap failure. Only a few studies explained the best time to perform lower extremity mobilization post free flap surgery to maintain adequate flap viability. This study aimed to find the effectiveness of the dangling protocol in reducing lower extremity free flap surgery complications. Methods: A literature search was conducted through PubMed, Cochrane, and Embase in March 2022 using “Free tissue flap” or “free flap” AND “dangling protocol” or “early ambulation” AND “postoperative complication” keywords. Title and abstract screening, full-text reading, and eligibility assessment were performed to find related evidence regarding our clinical question. Results:  The two relevant articles are a systematic review and a clinical trial study. Both studies showed 94-100% flap viability after applying early dangling protocol as early as three days post lower leg free flap surgery with level evidence of IIB up to IV without any incidence of flap necrosis. Conclusion: Early dangling protocol can be implemented safely after free flap surgery of the lower extremity without postoperative complications such as total or partial necrosis.